1988
DOI: 10.1063/1.99450
|View full text |Cite
|
Sign up to set email alerts
|

Reaction mechanisms in the organometallic vapor phase epitaxial growth of GaAs

Abstract: The decomposition mechanisms of AsH3, trimethylgallium (TMGa), and mixtures of the two have been studied in an atmospheric-pressure flow system with the use of D2 to label the reaction products which are analyzed in a time-of-flight mass spectrometer. AsH3 decomposes entirely heterogeneously to give H2. TMGa decomposes by a series of gas-phase steps, involving methyl radicals and D atoms to produce CH3D, CH4, C2H6, and HD. TMGa decomposition is accelerated by the presence of AsH3. When the two are mixed, as in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0
5

Year Published

1991
1991
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(83 citation statements)
references
References 13 publications
4
74
0
5
Order By: Relevance
“…Using helium or nitrogen instead, the decomposition temperature is 20-30 C higher [4][5][6]. Thus, using TMGa many methyl groups are present on the surface during growth, especially at lower temperatures.…”
Section: Introductionmentioning
confidence: 98%
“…Using helium or nitrogen instead, the decomposition temperature is 20-30 C higher [4][5][6]. Thus, using TMGa many methyl groups are present on the surface during growth, especially at lower temperatures.…”
Section: Introductionmentioning
confidence: 98%
“…In-rich growth conditions result in complete strain relaxation via interfacial 901 dislocations, which are twice as efficient in relieving the strain [20,21]. Ninety degree dislocations, which do not contribute to any tilt, are predominantly formed in case of small-sized ($few nm) InAs islands, relieving most of the misfit strain [19]. The early coalescence of such small islands, with an in-plane dislocation structure, would be promoted at low growth temperatures.…”
Section: Discussionmentioning
confidence: 96%
“…These lower growth temperatures affect both the thermally activated process of dislocation motion as well as the surface stoichiometry through changes in the surface chemical kinetics of the In and As precursors (TMIn and AsH 3 ). TMIn has a typical pyrolysis temperature of $300 1C [18] while AsH 3 is significantly more stable and will decompose significantly at temperatures of 500 1C and above [19]. Lower growth temperatures, at a fixed V/III ratio, result in an increase in the In-to-As ratio on the surface, which affects island nucleation and surface atomic transport.…”
Section: Discussionmentioning
confidence: 98%
“…The other possible source of hydrogen is of course the carrier gas. The work of Larsen et al using D2 as carrier gas demonstrated that the carrier gas is not involved in the reaction when both TMGa 4 arsine are present [31]. Previously we have shown that high overpressures of dihydrogen @I7) are required in order to produce a surface reaction leading to the of clean, yet ~s d e~i k t e d surfaces [20].…”
Section: The Chemistrv Of Arsine and Hvdrogen On Gaas (100) Surfacesmentioning
confidence: 99%